Pengolahan Kopi Bubuk dan Pemasaran Berbasis Digital Marketing dalam Meningkatkan Daya Saing Hilirisasi Kopi di Kawasan Lereng Menoreh - Masrukan Ahmad; Fahmi Rafika Perdana; Kristiana Sri Utami; Sri Lestari Harjanta (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
Diversification of post-havesting of coffe managed by the coffee farming group in the Sidoharjo district, Kulonprogo has several problems in post-harvest handling and processing coffee, especially in processing of coffee powder with good manufacturing process (gmp) as well as conventional marketing management. Through the Community Partnership Program (PKM), the service team provide solutions to outcome problems through several methods; 1) training and assistance in post-harvest handling 2) training and assistance in the production of ground coffee in a natural process and 3) training and assistance in marketing management with digital marketing. The results of the assistance are the post-harvest handling and processing of coffee properly and correctly by producing ground coffee with the brand name